Identifikasi Karakter Morfologi dan Agronomi Tanaman Gonda (Sphenoclea zeylanica Gaertn) di Kabupaten Jembrana, Bali - PERMADI, I WAYAN ADI; GUNADI, I GUSTI ALIT; SUKEWIJAYA, I MADE (Agrotrop : Journal on Agriculture Science, 2016)
The Identification of Morphological and Agronomic Characters of Gonda (Sphenocleazeylanica Gaertn) in Jembrana - Bali. Gonda (a local name) is a vegetable plant that has high nutritional value, however, limited information about this plant and related matters incultivation provide constraints in its development. Research concerning inventaritation and identification is required to support the development. The aim of the research was to find out information about the cultivation and characters of gonda. This research was conducted in October 2014 - March 2015 in Jembrana - Bali. Inventaritation was done through observation including deployment, history and cultivation method. While identification was done by identify morphological characters (vegetative and generative organs) and agronomic characters (height of plant and number of leaves). The results showed thats the gonda spread across rice fields at an altitude of 6 - 90 m AMSL. Gonda has been intensively cultivated since 1950 by farmers through seedling and planting. Various morphological and agronomic characters were identified among gonda planted by farmer in Jembrana, Bali. Based on the type of the branch, morphologically, gonda was grouped in to monopodial and sympodial. While for agronomic characters, a wide range of size and the number of organs were found among gonda cultivars planted by farmers in Jembrana.
Keywords: Sphenoclea zeylanica; identification; morphology; agronomic characters